Upaya Pengembangan Produk Melalui Branding Pada Produk Opak Dan Gula Cakar Di Desa Cieurih Kecamatan Maja Kabupaten Majalengka - Yelsha Dwi Pasca; Burhanudin Rabani; Vina Andita Pratiwi; Emi Amelia; Ade Sobariah Hasanah (PT. Berkah Digital Teknologi, 2025)
This community service records the results of the implementation of efforts to develop superior products from the Cieurih Village community to increase product marketing through branding strategies. A series of efforts to develop products by discussing how important branding a product is in facing increasingly tight business competition today. This method involves business actors by providing information related to branding to direct practice in product development with a focus on Opak and Gula Cakar Products in Cieurih Village. From the various efforts that have been made, it can be seen that branding a product has an impact on increasing product sales. In essence, product development efforts in the context of community service programs in Cieurih Village are able to provide insight and practical assistance for business actors, especially for Opak Ketan and Gula Cakar products in Cieurih Village, Maja District, Majalengka Regency. Abstrak Pengabdian masyarakat ini mencatat hasil implementasi upaya pengembangan produk unggulan masyarakat Desa Cieurih untuk meningkatkan pemasaran produknya melalui strategi branding. Serangkaian upaya untuk pengembangan produk dengan membahas bagaimana pentingnya Branding suatu produk dalam menghadapi persaingan bisnis yang semakin ketat saat ini. Metode ini dengan melibatkan pelaku usaha dengan memberian informasi terkait branding hingga praktik langsung dalam pengembangan produk dengan fokus pada Produk Opak dan Gula Cakar Desa Cieurih. Dari berbagai upaya yang telah dilakukan terlihat dengan adanya branding suatu produk berdampak pada peningkatan penjualan produk. Pada intinya upaya pengembangan produk dalam rangka program pengabdian masyarakat di Desa Cieurih mampu memberikan wawasan dan bantuan praktis bagi pelaku usaha khususnya produk Opak Ketan dan Gula Cakar Di Desa Cieurih Kecamatan Maja, Kabupaten Majalengka.